Convective boundary layer flow in generalized Newtonian nanofluid under various boundary conditions - Fayyadh Alshammari, Mohammed Mahdi (2021)
The four mathematical models of boundary layer flow solved under different boundary conditions. The first problem considered the unsteady squeezing flow of the Carreau nanofluid over the sensor surface, where three different nanoparticles were suspended in the base fluid. A comparison of the results of suspended materials in liquids proved that increased surface permeability leads to increased heat transfer. The second problem described the magnetohydrodynamics (MHD) Darcy-Forchheimer model, which considers Maxwell nanofluids' flow. It was observed that an increase in the Biot number coefficient increased heat transfer. The third problem evaluated activation energy and binary reaction effect on the MHD Carreau nanofluid model. Buongiorno nanofluid model was applied to shear-thinning or pseudoplastic fluid over the pereamble surface. The relationship between the activation energy and chemical reaction is influential and controls heat transfer processes. The fourth problem analyzed the radiative Sutterby model over a stretching/shrinking sheet towards stagnation point flow. Dual solutions were found using the scaling group transformation, which was examined by a stability approach. Such a problem found an increment in the suction parameter, the Deborah number, and the nanoparticle volume fraction delayed the flow separation. The influence of various pertinent parameters on the velocity and temperature distributions has been presented. The most relevant results by the forceful impacts of thermo-physical properties on fluids were analyzed through this work. Modeled equations are based on the conservation laws under the boundary layer approximation. The similarity transformation method is used to convert the governing partial differential equations into ordinary differential equations. They are then solved using a numerical technique, known as the RungeKutta-Fehlberg method with shooting technique in the MAPLE 17 or bvp4c method in the MATLAB 2019a.